2018
DOI: 10.1136/heartjnl-2018-313617
|View full text |Cite
|
Sign up to set email alerts
|

Extended treatment of venous thromboembolism: a systematic review and network meta-analysis

Abstract: ObjectiveTo evaluate efficacy and safety of oral anticoagulant regimens and aspirin for extended venous thromboembolism (VTE) treatment.MethodsWe searched MEDLINE, Embase, CENTRAL and conference proceedings for randomised controlled trials studying vitamin K antagonists (VKAs), direct oral anticoagulants (DOACs) or aspirin for secondary prevention of VTE beyond 3 months. ORs (95% credible intervals) between treatments were estimated using random-effects Bayesian network meta-analysis.ResultsSixteen studies, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
4
12
0
1
Order By: Relevance
“…We demonstrate that all DOACs exhibit comparable efficacy and are all superior to placebo for the prevention of recurrent VTE. Our findings suggest that DOACs can be used interchangeably for secondary prophylaxis of VTE, which is consistent with prior reports of DOACs for the prevention of recurrent VTE …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrate that all DOACs exhibit comparable efficacy and are all superior to placebo for the prevention of recurrent VTE. Our findings suggest that DOACs can be used interchangeably for secondary prophylaxis of VTE, which is consistent with prior reports of DOACs for the prevention of recurrent VTE …”
Section: Discussionsupporting
confidence: 92%
“…Second, the ease of use (oral administration without need of frequent laboratory monitoring) has prompted many clinicians to favour DOACs over VKA or LMWH in patients without contraindications or prohibitive costs . Third, prior analyses have demonstrated that DOACs may have similar efficacy for preventing recurrent VTE and a more favourable safety profile than VKA with respect to major bleeding . We recognize, however, that VKA or LMWH may remain favourable in some situations, such as in thrombosis associated with antiphospholipid syndrome, cancer‐associated thrombosis, end‐stage renal disease or liver disease, or lack of health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 26,872 VTE patients in modern acute VTE treatment trials (most treated for 6 months with one trial permitting treatment up to 1 year), van Es and colleagues showed that the risk of recurrent VTE during the acute treatment phase was~2% in DOAC and vitamin K antagonist (VKA) treated patients [14]. Also, in a long-term secondary prevention network meta-analysis Wang and colleagues calculated a pooled event rate of 1.2 per 100 person years with standard intensity VKA with comparable rates using other anticoagulant options [15]. Hence, the large majority of patients in the acute, sub-acute and long-term VTE treatment phases do not develop recurrent VTE, which in turn behooves us to ask why patients develop recurrent VTE.…”
Section: Consider the Etiology Of Recurrent Vte On Anticoagulantsmentioning
confidence: 99%
“…The answer to why a patient develops recurrent VTE might include the following: 1) Non-compliance-Given the high rates of recurrent VTE in patients in whom ongoing anticoagulation for secondary VTE prevention is warranted but not continued and the high relative risk reductions (> 80%) with adequate anticoagulation [14,15], it should not be surprising to find that non-compliance is likely a key etiology of "apparent treatment failure". Compliance with VKA is easy to measure and document with an INR at the time of the recurrent VTE.…”
Section: Consider the Etiology Of Recurrent Vte On Anticoagulantsmentioning
confidence: 99%
“…In patients who underwent HFS, it is recommended that the duration of drug prevention be at least 10 days and extendable to 11–35 days. Several studies have shown that extended prophylaxis substantially reduces the risk of VTE, and they recommend a longer prophylaxis duration in all patients undergoing major orthopaedic surgery. Due to the high risk of VTE after HFS, the UK‐based National Institute for Health and Clinical Excellence (NICE, 2018), Scottish Intercollegiate Guidelines Network (SIGN, 2009), the American College of Clinical Pharmacy (ACCP, 2012) and the American Academy of Orthopaedic Surgeons (AAOS, 2011) guidelines suggest that the use of low‐molecular‐weight heparin (LMWH) is preferable to other agents for prevention of thrombosis.…”
Section: Introductionmentioning
confidence: 99%